From bargaining solutions to claims rules: A proportional approach - José-Manuel Giménez-Gómez; António Osório; Josep E. Peris (Games, 2015)
Agents involved in a conflicting claims problem may be concerned with the proportion of their claims that is satisfied, or with the total amount they get. In order to relate both perspectives, we associate to each conflicting claims problem a bargaining-in-proportions set. Then, we obtain a correspondence between classical bargaining solutions and usual claims rules. In particular, we show that the constrained equal losses, the truncated constrained equal losses and the contested garment (Babylonian Talmud) rules can be obtained throughout the Nash bargaining solution.
Keywords: C71; D63; D71; 330; bargaining problem; conflicting claims problem; proportionality; bargaining solutions; claims rules